Analisis Pembelajaran Bisnis Online Dengan Menggunakan Model Pembelajaran Discovery, Problem Based, Dan Project Based Learning - Nursyam (Universitas Pancasakti Tegal, 2022)
This article discusses the application of the use of learning designs with three different models with the same material discussed. The three models include Problem Based Learning, Discovery Learning, and Project Based Learning. While the material discussed is material on the subject of Online Business Basic Competence / KD 3.4 Analyzing SEO On Page keywords and KD 4.4 Making SEO ON Page keywords. There are differences in the treatment of the three activities in achieving learning objectives. In Problem Based Learning to meet the target of student competence, both knowledge and skills, students are faced with problems related to the material and are invited to overcome existing problems. Problems in Problem Based Learning require an explanation of a phenomenon. The focus is on how students identify learning issues and then look for alternative solutions. In the discovery learning model, students are directed to understand concepts, meanings, and relationships through an intuitive process to finally arrive at a conclusion. Discovery is done through the stages of observation, classification, measurement, prediction, determination, and inference. And in Project Based Learning or student-centered learning project-based learning to conduct an in-depth investigation of a topic. Students constructively deepen with a research-based approach to serious, real, and relevant problems and questions.